1976
DOI: 10.1152/jappl.1976.41.5.797
|View full text |Cite
|
Sign up to set email alerts
|

Impedance cardiography for determination of stroke index

Abstract: Stroke index obtained by impedance cardiography was compared with values obtained by dye-dilution technique in 17 subjects in 122 determinations made within 2 min of each other. Fifty of these determinations were done after drug administration, postural change, or saline infusion. All values obtained by both methods correlated significantly, but with wide scatter (r=0.49, n = 122, P less than 0.001). The series of determinations within each subject, however, correlated only in one subject significantly; thus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

1983
1983
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Aust et al (1982) noted agreement between tilt-induced changes in stroke volume using the impedance method and echocardiography, and Boer et al (1979) reported similar results with thermodilution as the reference technique. In contrast, Keim et al (1976) reported poor agreement in tilt-associated changes in stroke index measured using the impedance and dye-dilution techniques.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Aust et al (1982) noted agreement between tilt-induced changes in stroke volume using the impedance method and echocardiography, and Boer et al (1979) reported similar results with thermodilution as the reference technique. In contrast, Keim et al (1976) reported poor agreement in tilt-associated changes in stroke index measured using the impedance and dye-dilution techniques.…”
Section: Discussionmentioning
confidence: 91%
“…This confirms the findings of several other groups (Boer et al, 1979;Denniston et af., 1976;Edmunds et al, 1982;Gabriel et af., 1976;Hayashi et af., 1978;Judy et al, 1969;Lababidi et al, 1971;Milsom et al, 1982Milsom et al, , 1983Naggar et al, 1975;Secher et al, 1977Secher et al, , 1979Smith et al, 1970;Tanguy et al, 1982). A few negative studies have also appeared (Keim et al, 1976;Enghoff & Lowheim, 1979). Practical factors may partially explain the negative findings as well as the imperfect agreement with the thermodilution technique.…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with the intra-cardiac fluid inversion [8], [23], [24]. The O point corresponds to the peak positive deflection in ICG after the X point [8] and it is associated with rapid filling of the ventricles during wider opening of the mitral valve [14], [23].…”
Section: Icg Characterisitc Pointsmentioning
confidence: 99%
“…In general, comparisons of impedance cardiography with well-established invasive techniques have shown high correlations when averaged across reasonably healthy subjects (20), although there has been some tendency to overestimate stroke volume (2,5,7,12,17). The correlations have been much poorer in some abnormal patient populations (6,8,15), and when applied in individual subjects (1,3). Thus, the practical value of impedance cardiography for critical care monitoring and diagnostic purposes in individual patients has not yet been realized.…”
Section: Introductionmentioning
confidence: 99%